APPLICABILITY OF THE ORDER CYCLE MANAGEMENT CONCEPTS IN A DIRECT RESALE MODEL OF COSMETICS - Aguiar, Laudiceia Gonçalves de; Herculani, Rhadler (Revista Interface Tecnológica, 2020)
The objective of this article is to understand the applicability of the direct resale order cycle in a cosmetics company, identifying its agents, and to suggest the application of service level management and logistics management concepts. It is understood that the success of supply chain management is linked to the integration of all processes related to the activities that involve the production, circulation and destruction of products and services between companies, their suppliers and customers. Therefore, the approach of the article is justified by the proximity of the direct selling business model in the daily lives of many people in our region, and the fact of identifying and applying logistical concepts can provide benefits for the economic development of society a return. For this, a qualitative bibliographic research and a real case study were used. The results showed that the problem of time variability is mainly related to the fact that the informality and simplicity of this type of product commercialization, in most cases, tools for standardization and control are not used. Thus, it is concluded that it is possible to apply logistic management concepts to small businesses, even if informal and poorly structured.